Effects of single food components on freeze concentration by freezing and thawing technique - Yee, Phang Lai; Wakisaka, Minato; Shirai, Yoshihito; Hassan, Mohd Ali (Japan Society for Food Engineering, 2003)
Effects of single food components such as sodium chloride, sugars and milk protein on freeze concentration by freezing and thawing treatment were evaluated in this study. This method has a different concept from traditional freeze concentration whereby complete freezing is essential prior to thawing. The concentrated fractions were separated upon thawing the frozen sample in a chamber at 10°C. Various thawing rates were obtained when thawing the food components of different concentrations. The concentration of the solute affects the freezing point depression of the aqueous solution. The concentration index was used to evaluate the effectiveness of freezing and thawing on concentrating the food components within the range of 1 to 20%. The 1% of sodium chloride, glucose, fructose, lactose and sucrose solutions were concentrated 4-5 times in the first fraction, except dextrin (less than 2. 5 times). As the concentration of the food components increased, the concentration effect reduced as shown by the reducing index approaching unity. However, dextrin and milk protein solutions were not effectively concentrated by freezing and thawing due to their smaller freezing point depression.